Improving survival rates of newborn infants in South Africa - Greenfield David; Woods David; Pattinson Robert; Velaphi Sithembiso (BMC, 2005)
Abstract Background The number, rates and causes of early neonatal deaths in South Africa were not known. Neither had modifiable factors associated with these deaths been previously documented. An audit of live born infants who died in the first week of life in the public service could help in planning strategies to reduce the early neonatal mortality rate. Methods The number of live born infants weighing 1000 g or more, the number of these infants who die in the first week of life, the primary and final causes of these deaths, and the modifiable factors associated with them were collected over four years from 102 sites in South Africa as part of the Perinatal Problem Identification Programme. Results The rate of death in the first week of life for infants weighing 1000 g or more was unacceptably high (8.7/1000), especially in rural areas (10.42/1000). Intrapartum hypoxia and preterm delivery are the main causes of death. Common modifiable factors included inadequate staffing and facilities, poor care in labour, poor neonatal resuscitation and basic care, and difficulties for patients in accessing health care. Conclusion Practical, affordable and effective steps can be taken to reduce the number of infants who die in the first week of life in South Africa. These could also be implemented in other under resourced countries.